Emerging AI Regimes and Contemporary Filmmaking in Nigeria: Governance, Practice, and Creative Futures (Architecture Image Studies, 2025)
Filmmaking is rapidly transforming by Artificial Intelligence (AI) across the globe, with Nigeria’s vibrant film industry (i.e. Nollywood) emerging as an adopter and a contested site for technological experimentation. How technological, institutional, and regulatory frameworks as emerging AI regimes are reforming creative practices and industry structures in Nigeria is examined in this study. Also, the integration of AI tools was explored in this study across pre-production, production, post-production, and distribution by situating Nollywood within global discourses of platform capitalism and algorithmic governance. The study highlights several case studies such as AI-enabled editing, subtitling, visual effects, and distribution on digital platforms. It addresses the challenges in governance related to intellectual property, labor, and cultural representation. The study, by drawing on a multi-level framework of AI regimes, emphasizes that in time to come, Nigerian filmmaking will depend on innovation that is balanced with protections for creative labor and cultural integrity. The study concludes by recommending policies and practices for building a comprehensive, sustainable AI-enabled film ecosystem in Nigeria and Africa in general.